Reperfusion Into Severely Damaged Brain Tissue Is Associated With Occurrence of Parenchymal Hemorrhage for Acute Ischemic Stroke - Yu, Songlin; Ma, Samantha J.; Liebeskind, David S.; Qiao, Xin J.; Yan, Lirong; Saver, Jeffrey L.; Salamon, Noriko; Wang, Danny J. J. (Frontiers in Neurology, 2020)
Background and Purpose—This study aims to quantify the reperfusion status within severely damaged brain tissue and to evaluate its relationship with high grade of hemorrhagic transformation (HT). Methods—Pseudo-continuous ASL was performed along with DWI in 102 patients within 24 hours post treatments. The infarction core was identified using ADC values less than 550×10−6 mm2/s. CBF within the infarction core and its contralateral counterpart was acquired. CBF at the 25th, median, and 75th percentiles of the contralateral counterpart was used as thresholds and the ASL reperfusion volume above the threshold was labeled as vol-25, vol-50 and vol-75 respectively. Recanalization was defined according to Thrombolysis In Myocardial Infarction (TIMI) criteria. Results— Quantified reperfusion within the infarction core differs significantly in patients with complete and incomplete recanalization. Both ADC threshold volume and ASL reperfusion volume at all three percentiles differed significantly between HT categories such as HT vs. no HT, Parenchymal hematoma (PH) vs. no PH and PH-2 vs. no PH-2. In the ROC analysis for the prediction of parenchymal hematoma (PH) , ASL reperfusion vol-25 has the highest area under the curve (AUC) when compared with ASL vol-50 and ASL vol-75. ASL reperfusion vol-25 had significantly higher AUC compared with ADC threshold volume in the prediction of PH (0.783 vs.0.685, P=0.00360.782 vs. 0.679, P=0.002) and PH-2 (0.844 vs. 0.754, P=0.00350.844 vs. 0.749, P=0.0027). In stepwise multivariate logistic regression analysis, only ASL reperfusion vol-25 emerged as an independent predictor of PH (OR=3.51, 95% CI 1.65-7.45, P<0.001OR=3.62, 95% CI 1.71-7.64, P=0.001) and PH-2 (OR=2.32, 95% CI 1.13-4.76, P=0.022OR=2.34, 95% CI 1.14-4.80, P=0.02). Conclusions—Increased reperfusion volume within severely damaged brain tissue is associated with the occurrence of impending higher grade of HT.